Out-of-hospital cardiac arrest survivors with cognitive impairments have lower exercise capacity. (June 2017) - Boyce, Liesbeth W.; Reinders, Carlien C.; Volker, Gerard; Los, Esther; van Exel, Henk J.; Vliet Vlieland, Thea P.M.; Goossens, Paulien H.
Abstract: Background: Hypoxic brain injury is described in up to 40% of survivors after out-of-hospital cardiac arrest (OHCA). Besides cognitive impairments, lack of circulation may also affect exercise capacity. It is not known if exercise capacity of patients with cognitive impairments differs from other OHCA survivors. Methods: This retrospective cohort study included patients ≥18 years with myocardial infarction (MI) as cause of OHCA admitted for cardiac rehabilitation between February 2011 and April 2014. Data in socio-demographic, OHCA and medical interventions were retrieved. Cognitive functioning was determined with the Mini-Mental State Examination, Cognitive Failures Questionnaire and the Informant Questionnaire on Cognitive Decline in the Elderly. Exercise capacity (VO2peak), workload (Watts) and blood pressure (mmHg) were measured at maximum cardiopulmonary exercise. Heart rate (bpm) was measured at rest and maximum exercise and Metabolic Equivalents of Tasks (MET) were calculated. Results: 65 patients after OHCA caused by MI were included (85% male, median age 60 years). Of 53 patients Cardio Pulmonary Exercise Test data was available of which nine patients showed cognitive impairments. Significant differences (p < 0.05) in exercise capacity were found between patients with and without cognitive impairments: VO2 peak (median 14.5 vs 19.7 ml/kg/min), workload (median 130.0 vs 143.5 W) and MET's (median 4.1 vs 5.6). Conclusion: Based on this small study, there seems to be a correlation between cognitive impairments and lower exercise capacity in patients referred for rehabilitation after OHCA caused by MI. It seems sensible for rehabilitation programs to take the lower exercise capacity of patients with cognitive impairments into account.